2013
DOI: 10.26719/2013.19.10.899
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension among young adult females in Dammam, Saudi Arabia

Abstract: A case of vocal tic: an unusual presentation of neurobrucellosis 1.Bahyan GI et al. A case of vocal tic: an unusual presentation of neurobrucellosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 25 , 26 ] Indeed, previous research from the Eastern Province of Saudi Arabia demonstrated that behavioral aspects could explain the probable cause of the increase in BMI and blood pressure in early life. These factors included physical inactivity, eating habits, especially high salt intake, [ 27 ] fructose aerated beverages and energy drink consumption, [ 28 ] physical inactivity, [ 29 ] and obesity. [ 15 ] In addition, increased TV viewing, use of smart tools, and sleep duration at a young age have been linked to an increased risk of being obese.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 26 ] Indeed, previous research from the Eastern Province of Saudi Arabia demonstrated that behavioral aspects could explain the probable cause of the increase in BMI and blood pressure in early life. These factors included physical inactivity, eating habits, especially high salt intake, [ 27 ] fructose aerated beverages and energy drink consumption, [ 28 ] physical inactivity, [ 29 ] and obesity. [ 15 ] In addition, increased TV viewing, use of smart tools, and sleep duration at a young age have been linked to an increased risk of being obese.…”
Section: Discussionmentioning
confidence: 99%
“…Primary prevention measures, with a focus on decreasing avoidable risk factors such as high blood pressure and body weight, may be the most effective approach for the prevention and control of CVD [ 14 ]. Prehypertension is defined as the transient stage between normal and high blood pressure (120–139/80–89 mmHg) and a risk factor for developing hypertension and target organs damage.…”
Section: Introductionmentioning
confidence: 99%